Water Hyacinth Management Due to Eutrophication in Water Bodies Around Pasir Panjang Village, Batam City - Adicita, Yosef; Afifah, Anshah Silmi; Ulfah, Nurul; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Universitas Islam Lamongan, 2022)
Water is a human need to carry out activities ranging from daily essentials to agricultural needs and others. Domestic wastewater must meet physical, chemical, and biological requirements so that humans cannot be polluted by the water, especially the water around the Pasir Panjang Village area in Batam, Riau Islands. This study aims to determine the potential use of water hyacinth for environmental health. This research was conducted by direct observation and measurement of water quality by grab sampling. Observation results show that not all residents use septic tanks as wastewater treatment results from daily activities. Some residents drain their wastewater directly into water bodies or surrounding land, resulting in decreased environmental aesthetics. Water quality testing for nutrient parameters shows that the quality standards have been met. However, further measurements are needed for total nitrogen and phosphate. Besides that, it also causes a population explosion of water hyacinth. In addition to the ability to treat water hyacinth waste, its economic potential is also analyzed. The growth of water hyacinth is sufficient and fulfills its capacity, and water hyacinth can be used for various crafts that can improve the community's welfare.